2017
DOI: 10.1016/j.actbio.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Modulating microfibrillar alignment and growth factor stimulation to regulate mesenchymal stem cell differentiation

Abstract: The ideal tissue engineering (TE) strategy for ligament regeneration should recapitulate the bonecalcified cartilage -fibrocartilage -soft tissue interface. Aligned electrospun-fibers have been shown to guide the deposition of a highly organized extracellular matrix (ECM) necessary for ligament TE.However, recapitulating the different tissues observed in the bone-ligament interface using such constructs remains a challenge. This study aimed to explore how fiber alignment and growth factor stimulation interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 70 publications
1
51
0
Order By: Relevance
“…Oliveira et al studied the differentiation of bone marrow-derived porcine mesenchymal stem cells in ligament or bone/cartilage differentiation, using random and aligned microfibers of PCL. They added different growth factors to study the differentiation of cells in ligamentogenic, chondrogenic or fibrochondrogenic phenotype upon presentation of appropriate biochemical cues [ 90 ]. Wu et al focused on the repair of the tendon-to-bone and ligament-to-bone insertions: they analyzed nanostructured HAp, loaded in random nanofibrous blends mats of PCL and CTS.…”
Section: Applications For Tendon and Ligament Regeneration And Repmentioning
confidence: 99%
“…Oliveira et al studied the differentiation of bone marrow-derived porcine mesenchymal stem cells in ligament or bone/cartilage differentiation, using random and aligned microfibers of PCL. They added different growth factors to study the differentiation of cells in ligamentogenic, chondrogenic or fibrochondrogenic phenotype upon presentation of appropriate biochemical cues [ 90 ]. Wu et al focused on the repair of the tendon-to-bone and ligament-to-bone insertions: they analyzed nanostructured HAp, loaded in random nanofibrous blends mats of PCL and CTS.…”
Section: Applications For Tendon and Ligament Regeneration And Repmentioning
confidence: 99%
“…Cytoskeleton staining revealed fibrosis in the stem cells isolated from mildly and severely degenerated LZAC, indicating that the mesochondrial environment altered the characteristics of these cells to some extent (30,31). Subsequent experiments suggested that stem cells isolated from mildly degenerated LZAC exhibited enhanced chondrogenic differentiation and clonogenic abilities compared with those from normal LZAC.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the introduction of biochemical cues on biomaterial surface is a successful way to efficiently induce specific cell behavior such as cell survival, cell differentiation or cell growth (Li and Folch, ; Krick et al, ). The stimulation with growth factors combined with fibre substrate has demonstrated its efficacy for different biological processes, among which nerve regeneration (Bruggeman et al, ; Olvera et al, ), and specific growth factors might be used to guide the axonal growth of specific neuron population. Here, we tested individually several growth factors, whose receptors are expressed in different sensory neuron populations.…”
Section: Discussionmentioning
confidence: 99%